Behind the Screen: Investigating Social Media Addiction and Stress as Explanatory Factors for Smartphone Distraction in Young Adults and Adults - Centella Centeno, Daniel Martin (2024)
The purpose of this study is to evaluate the fit of the model that relates distraction by the use of smartphones with addiction to social networks and stress in young people and adults in the department of Tacna in the year 2024. The research adopts an experimental design and has a sample of 100 participants from Tacna, selected through non-probabilistic sampling. The results obtained reveal an X2/gl of 15.01, a CFI of 0.993, a TLI of 0.990, an RMSEA of 0.376, an SRMR of 0.053 and a PNFI of 0.767. In conclusion, it is evident that the adjustment model relating smartphone distraction with social network addiction and stress in young people does not reach adequate goodness-of-fit indices.